Effect of Er,Cr:YSGG laser irradiation and self-etch adhesive systems on hypermineralized dentin: A bond strength evaluation - Da Costa Neves, Tamíris [UNESP] (2020)
Over time teeth are exposed to several physical-chemical alterations, which may change the dental structure. Therefore, dental clinicians must be aware of how to manage the altered tissue. Laser irradiation and self-etch adhesives may be an option in this situation. This study aimed to evaluate the bond strength of self-etch adhesive systems associated with different treatments on hypermineralized dentin. 80 bovine incisors were distributed into two groups: Universal (3M ESPE; n = 40) and Optibond All in One (Kerr; n = 40). Five treatments were performed for each group (n = 8): (T1) adhesive system (control); (T2) acid + adhesive; (T3) Er,Cr:YSGG laser + adhesive; (T4) acid + Er,Cr:YSGG laser + adhesive; (T5) Er,Cr:YSGG laser + acid + adhesive. After bond and restorative procedures, teeth were submitted to microshear bond strength test. ANOVA two-way followed by Games-Howell Test was performed. Statistical significance difference was observed for adhesive systems and treatments (p 0.001). For the adhesives used, Universal adhesive system presented the highest average bond strength. The highest bond strength was obtained in the control group (T1), T3 and T4. Laser irradiation may be a viable option as a surface pretreatment on hypermineralized dentin when self-etch adhesives are used.